AGING IN THE TROPICS: THE POSITION OF OLDER PERSONS IN THE INTER-AMERICAN HUMAN RIGHTS SYSTEM - Holtermann, João Gabriel Wibelinger; Wibelinger, Lia Mara; Morette, Isabela (Seven Editora, 2026)
The present study aims to establish a brief overview of the position of older persons and the recognition of their rights as fundamental guarantees within the Inter-American human rights system. Based on the understanding of human aging as a natural, continuous, multifactorial process that is rapidly increasing in Latin American and Caribbean countries, this study seeks to analyze how these States are addressing the growing elderly population in light of the international commitments undertaken at the regional level within the Organization of American States (OAS) and at the global level within the United Nations (UN). By outlining a historical framework of the evolution of this issue within the legal instruments that make up the Inter-American human rights system—from the Protocol of San Salvador of 1988 to the Inter-American Convention on the Protection of the Human Rights of Older Persons of 2015—the study aims to extract from these documents the reference framework through which older persons and the phenomenon of aging are viewed by OAS member States, with particular emphasis on Brazil’s position in the debate on the human rights of older persons and the improvement of public policies aimed at individuals undergoing the aging process.DOI: https://doi.org/10.56238/sevened2026.008-054